PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING BERBANTUAN MEDIA SMARTBOARD DALAM MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SDN TINGGIRAN DARAT - Muhammad Hendra Aprian Nur; Rahidatul Laila Agustina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low learning activities and learning outcomes of fourth-grade elementary school students in Pancasila Education indicate the need for innovative learning strategies that actively engage students. This study aimed to improve students' learning activities and learning outcomes on the topic of Unity and Integrity through the implementation of the Role Playing learning model assisted by Smartboard media. The research employed Classroom Action Research (CAR) using the Arikunto model, consisting of planning, action, observation, and reflection stages conducted in two cycles. The participants were 17 fourth-grade students of SDN Tinggiran Darat, Barito Kuala Regency. Data were collected through observation, tests, and documentation, and analyzed using descriptive qualitative and quantitative techniques. The findings revealed a continuous improvement in the learning process. Teacher activity increased from 61% in the first meeting of Cycle I to 98% in the second meeting of Cycle II. Student activity also improved from 64% to 96%. Furthermore, students' learning mastery increased significantly from 29.41% in the pre-action stage to 100% at the end of Cycle II. These findings indicate that the implementation of the Role Playing learning model assisted by Smartboard media effectively improves both learning activities and learning outcomes in Pancasila Education for fourth-grade elementary school students.